Multiple Cutaneous Angiosarcomas after Breast Conserving Surgery and Bilateral Adjuvant Radiotherapy: An Unusual Case and Review of the Literature - Icro Meattini; Raffaella Santi; Daniele Scartoni; Irene Giacomelli; Carla De Luca Cardillo; Vieri Scotti; Donato Casella; Roberta Simoncini; Lorenzo Orzalesi; Jacopo Nori; Milena Paglierani; Lorenzo Livi (Case Reports in Oncological Medicine)
Breast angiosarcomas (BAs) are rare but serious events that may arise after radiation exposure. Disease outcome is poor, with high risk of local and distant failure. Recurrences are frequent also after resection with negative margins. The spectrum of vascular proliferations associated with radiotherapy in the setting of breast cancer has expanded, including radiation-associated atypical vascular lesions (AVLs) of the breast skin as a rare, but well-recognized, entity. Although pursuing a benign behavior, AVLs have been regarded as possible precursors of postradiation BAs. We report an unusual case of a 71-year-old woman affected by well-differentiated bilateral cutaneous BA, diagnosed 1.9 years after adjuvant RT for synchronous bilateral breast cancer. Whole-life clinical followup is of crucial importance in breast cancer patients.